Atividades estimuladoras de leitura e escrita em estudantes com síndrome de Down - Comin, Bruna Cristina (Universidade Federal de São Carlos, 2013)
Literature presents that students with Down Syndrome (DS) learn to write and read in a slower pace than students without the disability. From these considerations, the present work considers the following question: to what extent the proposition and application of stimulator activities of the reading and writing, based on Emília Ferreiro theory, about the four levels of writing develops and enhances the knowledge of a young DS group? To answer this question, the present study was divided into two stages. In Stage one the goal was to conduct a survey of Dissertations, Theses and Articles (national and international) concerning the DS thematic, focusing on reading, writing and literacy in the period from 2001 to 2011. Bibliographic research was used. The tools used for search were: Portal Capes, SciELo, Google Scholar e Journal Portal Capes. In short, the life sciences showed a large concentration of Dissertations, Theses and Articles in Biological area, followed by the Humanities. In Stage two the goals was to investigate the acquisition of reading and writing of a young DS group from a specialized institution, checking on what level of writing and reading it was. The case study had six young DS participants, being two of the male gender and four of the female. Fictitious names were used to preserve their identity. The tools used for the research were: notes of interventions; document of activities developed on week; document of students attendance; Test of the 4 words and one phrase ; An adapted test from a new magazine (Test of reading); Literacy Pre-syllabic Program; Literacy Syllabic Program; and Literacy Syllabic-alphabetic Program. The materials used were assembled to provide functional support for the proposed activities. After prior approval by the Ethics Committee, the data collection was done thought three testes and a number of intervention sessions. The data was qualitatively analyzed for the identification of an evolution (or not) in writing and reading of the students. A quantitative analysis was also done trough a compilation of data about the reading aptitude of students who were in syllabic and syllabic-alphabetic level. Results were divided in three parts: writing of the name; writing of four words and a phrase; and textual reading. Fabiana regarding the writing of the name passed from syllabic level to syllabic-alphabetic; regarding the writing of four words and a phrase passed too from syllabic level to syllabic-alphabetic; regarding textual reading passed from 20% to 51% of reading units present inside the text. Raquel regarding the writing of the name and regarding the writing of four words and a phrase stayed on pre-syllabic level, showing improvement in her fine motor skills; regarding textual reading she started to identify letters A, I, O U. Lucas regarding the writing of the name and regarding the writing of four words and a phrase stayed on pre-syllabic level, but began to write down the letter A; regarding textual reading the student didn t identify any letter. Talita regarding the writing of the name passed from syllabic-alphabetic level to alphabetic; regarding the writing of four words and a phrase stayed on pre-syllabic level (initially presenting differentiation between words , with posterior differentiation between words and letters ); regarding textual reading started to recognize letter E, besides further the others that she already knew. Ricardo regarding the writing of the name and regarding of writing of four words and a phrase keep on pre-syllabic level, starting to write letter A and I; regarding textual reading on the first test identified letter A and on the final test the letters A, E, I, O and U. Rose regarding the writing of the name stayed on alphabetic level; regarding the writing of four words and a phrase passed syllabic-alphabetic level to alphabetic level; regarding textual reading improved from 51,1% to 64% the reading of the units presents inside the text. To summarize, the structure activities helped the young DS students to improve their reading and writing, given that stimulating activities of reading and writing were always concrete and/or adapted. Therefore, the students learned.
Keywords: Educação Especial; Down, Síndrome de; Jovens; Leitura e escrita; Special Education; Down Syndromes young; Read and Write; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL